Self-reactive IgE and anti-IgE therapy in autoimmune diseases - Olewicz-Gawlik, Anna; Kowala-Piaskowska, Arleta (Frontiers in Pharmacology, 2023)
Growing evidence indicates the pathogenic role of autoreactive IgE in autoimmune diseases. Incidence of autoimmune and allergic diseases in the industrialized countries is consistently icreasing, thus leading to concerted efforts to comprehend the regulation of IgE-mediated mechanisms. The first reports of a presence of IgE autoantibodies in patients with autoimmune diseases have been published a long time ago, and it is now recognized that self-reactive IgE can mediate inflammatory response in bullous pemhigoid, systemic lupus erythematosus, chronic urticaria, and atopic dermatitis. The advances in understanding the pathomechanisms of these disorders brought to a successful use of anti-IgE strategies in their management. The present review discusses the current state of knowledge on the IgE-mediated autoimmunity and anti-IgE treatment, and pave the way for further exploration of the subject.